Deodorant fiber structure

JP2025041826AActive Publication Date: 2025-03-26東レライクラ株式会社
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024227392
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-05-19
Filing Date
2024-12-24
Publication Date
2025-03-26
Estimated Expiration
2041-03-24

AI Technical Summary

Benefits of technology

【0007】 本発明は、ポリマーに無機層状消臭剤を混合した消臭繊維を含む消臭性繊維構造物であって、前記無機層状消臭剤は、層間距離が0.1nm以上0.9nm以下であり、かつ結晶子サイズが1nm以上30nm以下であり、前記消臭性繊維構造物は、家庭洗濯0回と10回後のアンモニアガス減少率がいずれも70%以上であることにより、消臭性能が高く耐洗濯性も高い消臭性繊維構造物を提供できる。すなわち、無機層状消臭剤を混合した消臭繊維を含む漂白処理前の消臭性繊維構造物はアルカリ処理すると層間距離が0.9nmを越え消臭機能が著しく低下するが、有機酸処理により前記消臭剤の層間距離が0.9nm以下となり、消臭機能が復活した、漂白された消臭性繊維構造物が得られる。この消臭性繊維構造物の消臭機能は耐洗濯性も良好である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025041826000001_ABST
    Figure 2025041826000001_ABST
Patent Text Reader

Abstract

To provide a deodorant fiber structure having high washing resistance in spite of being bleached.SOLUTION: A deodorant fiber structure comprises deodorant fibers obtained by mixing an inorganic layered deodorant with a polymer, wherein the inorganic layered deodorant has an interlayer distance of 0.1 nm or more and 0.9 nm or less and a crystallite size of 1 nm or more and 30 nm or less, and the deodorant fiber structure has an ammonia gas reduction rate of 70% or more after 0 and 10 home washings. The inorganic layered deodorant is preferably at least one selected from α-zirconium phosphate, α-hafnium phosphate, and α-titanium phosphate.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a deodorizing fiber structure having high deodorizing performance and high washability. [Background technology]

[0002] Deodorizing fibers are used in carpets, curtains, bedding, underwear, diapers, sanitary products, etc., and since clothing, which comes into direct contact with the skin, can cause discomfort due to odors such as sweat and body odor, there is a high demand for textile products with deodorizing functions. Patent Document 1 proposes knitting using elastic fiber and crosslinked acrylate yarn containing carboxyl groups and crosslinked bonds by hydrazine treatment as a deodorant fiber. Patent Document 2 proposes elastic fiber containing zinc oxide and zirconium phosphate. Patent Document 3 proposes synthetic fiber containing α-zirconium phosphate and / or α-titanium phosphate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-000659 A [Patent Document 2] JP 2006-028453 A [Patent Document 3] JP 2018-178313 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] However, crosslinked acrylate yarns such as those in Patent Document 1 have a high hygroscopicity, and there is a problem in that the deodorizing function is not exhibited when moisture or water is absorbed. Also, the fibers in Patent Documents 2 and 3 have a problem in that the deodorizing function is lost when they are treated with alkali. Alkali treatment is used in the case of polyester fibers in an alkali weight reduction process, and in the case of cotton fibers, hemp fibers, etc., in the process of scouring, bleaching, bleaching, and mercerizing (mercerizing) processing, and the loss of deodorizing function is a problem.

[0005] The present invention solves the above-mentioned problems of the prior art and provides a deodorizing fiber structure which has been bleached and yet has high washing resistance. [Means for solving the problem]

[0006] The deodorizing fiber structure of the present invention is a deodorizing fiber structure comprising a deodorizing fiber in which an inorganic layered deodorizer is mixed with a polymer, the inorganic layered deodorizer having an interlayer distance of 0.1 nm or more and 0.9 nm or less and a crystallite size of 1 nm or more and 30 nm or less, and the deodorizing fiber structure has an ammonia gas reduction rate of 70% or more both after 0 home washing and after 10 home washings. Effect of the Invention

[0007] The present invention provides a deodorizing fiber structure containing a deodorizing fiber in which an inorganic layered deodorant is mixed with a polymer, the inorganic layered deodorant having an interlayer distance of 0.1 nm to 0.9 nm and a crystallite size of 1 nm to 30 nm, and the deodorizing fiber structure has an ammonia gas reduction rate of 70% or more after 0 and 10 home washes, thereby providing a deodorizing fiber structure with high deodorizing performance and high washability. That is, when a deodorizing fiber structure containing a deodorizing fiber mixed with an inorganic layered deodorant is treated with an alkali, the interlayer distance exceeds 0.9 nm and the deodorizing function is significantly reduced, but when the deodorizing fiber structure is treated with an organic acid, the interlayer distance of the deodorant becomes 0.9 nm or less, and a bleached deodorizing fiber structure with restored deodorizing function can be obtained. The deodorizing function of this deodorizing fiber structure is also good in washability. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a multi-plot graph of wide-angle X-ray diffraction patterns of an inorganic layered deodorant used in one embodiment of the present invention, and is an enlarged view of the vicinity of 2θ=10°. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present inventors came across the problem that elastic fibers containing inorganic layered deodorants such as α-zirconium phosphate initially have deodorant properties, but when treated with alkali, the deodorant properties are lost, and investigated the cause. The layer structure of α-zirconium phosphate is as shown below (Chemical formula 1), and the interlayer distance is about 7.55A (angstroms, 0.755 nm) (Hasegawa Yoshinori et al., "On the ion exchange properties of layered phosphate M(IV)(HPO4)2·H2O (M=Zr, Hf)", IONICS, October 1985 issue).

[0010] [ka]

[0011] The interlayer distance of the α-zirconium phosphate is capable of trapping substances with molecular sizes smaller than ammonia, and it is presumed that the trapped gas is neutralized and deodorized by ionic bonding with the functional groups of the α-zirconium phosphate crystals. However, it was found that when a fiber structure is placed under strong alkaline conditions such as alkali treatment, the interlayer distance of 0.9 nm is expanded due to ion exchange with alkali metals, etc., and substances other than ammonia are also incorporated, the active functional groups decrease, and the deodorizing function is lost. Therefore, various studies were conducted to restore the deodorizing function, and it was found that the interlayer distance of the inorganic layered deodorant can be returned to its original state by performing an organic acid treatment after alkali treatment, and the deodorizing function is also restored. The experimental conditions and results will be explained later, but the important points are as shown in Table 1 below.

[0012] [Table 1]

[0013] As is clear from Table 1, the interlayer distance and crystallite size of α-zirconium phosphate become larger after scouring and bleaching, but the interlayer distance returns to the original state and the crystallite size becomes smaller than the original state by organic acid treatment. This is a novel finding. The present invention has been completed based on the above ideas and problems.

[0014] The present invention is a deodorizing fiber structure including a deodorizing fiber in which an inorganic layered deodorant is mixed with a polymer. As an example, a fiber obtained by adding and mixing an inorganic layered deodorant with a spinning solution is used. Spinning may be melt spinning or wet spinning. The deodorizing fiber structure is alkali-treated. In the case of polyester fibers, the alkali treatment is used in alkali weight reduction processing. In the case of cotton fibers, hemp fibers, etc., it is used in refining, bleaching, bleaching, and mercerization processing (mercerization processing). The amount of the inorganic layered deodorant added to the deodorizing fiber is preferably 0.5 to 10 mass %, and more preferably 1 to 7 mass %, when the deodorizing fiber is used as a modulus. Within the above range, high deodorizing properties can be maintained.

[0015] The fiber structure is treated with an organic acid after being treated with an alkali, and the deodorant has an interlayer distance of 0.9 nm or less, and the ammonia deodorizing properties after 0 and 10 home washings are 70% or more. The deodorant preferably has an interlayer distance of 0.70 to 0.85 nm, more preferably 0.72 to 0.80 nm. This results in a deodorant fiber structure with high deodorizing performance and high washability. In addition, when the deodorant is treated with an organic acid, the bonds of alkali metals such as sodium and potassium are eliminated from the deodorant, and the deodorant's deodorizing function is restored. The deodorant is preferably at least one selected from α-zirconium phosphate, α-hafnium phosphate, and α-titanium phosphate. The deodorant effects of α-zirconium phosphate and α-titanium phosphate are recognized in the above-mentioned Patent Document 3. The source document of the above-mentioned (Chemical Formula 1) describes that the interlayer distance of α-hafnium phosphate is equivalent to that of α-zirconium phosphate. Among these, α-zirconium phosphate is preferable.

[0016] The deodorant fiber is preferably at least one selected from synthetic fibers and regenerated fibers. The polymer constituting the deodorant fiber may be a thermoplastic resin such as polyester, polyamide, polyolefin, polyurethane, or a thermosetting resin such as regenerated cellulose or acrylic polymer. These resins can be mixed with the inorganic layered deodorant in the spinning solution. Regenerated fibers include rayon, cupra, polynosic, Lyocell (registered trademark), etc. Any spinning solution that can be mixed with the inorganic layered deodorant can be used.

[0017] The textile structure contains 100% by mass of the deodorizing fiber or the deodorizing fiber and other fibers. When the other fibers are contained, the deodorizing fiber is preferably 1 to 99% by mass when the textile structure is used as the parameter. More preferably, the deodorizing fiber is 2 to 50% by mass, and even more preferably, the deodorizing fiber is 5 to 30% by mass. If the content is within the above range, the deodorizing properties can be exhibited. The other fibers are preferably at least one selected from natural fibers, synthetic fibers, and regenerated fibers. Natural fibers include cotton, hemp, wool, silk, etc.

[0018] The organic acid is preferably an organic acid having 2 to 6 carbon atoms and containing a carboxyl group. The organic acid is effective in restoring the deodorant. In addition, it can be made into an aqueous solution, which is convenient for processing. The organic acid having 2 to 6 carbon atoms and containing a carboxyl group is preferably at least one selected from citric acid, maleic acid, malic acid, acetic acid, and succinic acid. When optical isomers are present, they are also included. Citric acid has the structure shown below (Chemical Formula 2). [ka] Maleic acid has the structure shown below (Chemical Formula 3). [ka] Malic acid has the structure shown below (Chemical Formula 4). [ka] Acetic acid has the structure shown below (Chemical Formula 5). [ka] Succinic acid has the structure shown below (Chemical Formula 6). [ka]

[0019] The fabric pH of the fiber structure is preferably 4.0 to 5.8, and more preferably 4.1 to 5.5. The fabric pH being on the weak acidic side is gentle on the skin and does not have any adverse effects. The fabric pH is measured according to the "Fabric Testing Method for Woven and Knit Fabrics" specified in JIS L1096:2010 8.37.

[0020] The ammonia deodorizing property of the fiber structure after 10 home washings is preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. This makes it possible to obtain a deodorizing fiber structure with high deodorizing performance and high washability. The home washing method and ammonia deodorizing property test will be described later.

[0021] In the present invention, the fiber structure may have any structure or shape, for example, a fabric-like material, a belt-like material, a string-like material, a thread-like material, etc. Preferably, a material containing a fabric-like woven or knitted fabric or a nonwoven fabric is used, and a material containing a composite material containing such a fiber structure may be used.

[0022] The fiber structure according to one embodiment of the present invention includes elastic fiber and at least cotton, and may include other fibers such as synthetic fiber, regenerated fiber, semi-synthetic fiber, and natural fiber other than cotton. When the fiber structure is used as a parameter, the ratio of elastic fiber to cotton is preferably 1 to 30 mass% for elastic fiber and 70 to 99 mass% for cotton. When cotton is used as a parameter, it is preferably 10 to 90 mass% for cotton and 10 to 90 mass% for fibers other than cotton.

[0023] Examples of synthetic fibers include polyester fibers, polyamide fibers, polyethylene fibers, polypropylene fibers, polyvinyl alcohol fibers, polyvinyl chloride fibers, and polyacrylonitrile fibers. Examples of polyester fibers include polyethylene terephthalate, polybutylene terephthalate, and polytrimethylene terephthalate, and examples of fibers copolymerized with a third component such as isophthalic acid. Examples of regenerated fibers and semi-synthetic fibers include rayon and acetate, and examples of natural fibers include hemp, wool, and silk. These fibers may be either short or long fibers, and can be used alone or in combination of two or more types as mixed fibers, mixed spinning, or composite processed yarns. These synthetic fibers or natural fibers can also be used as composite processed yarns such as covering, air entanglement, plying, composite false twisting, and core spun yarns with elastic fibers made of polyurethane.

[0024] The fiber structure is preferably a knitted fabric, a woven fabric, or a garment sewn therefrom. In particular, the knitted fabric is suitable for stretchable garments such as leg wear, innerwear, sportswear, and socks. It can also be used for diapers, sanitary napkins, etc. These are required to have high deodorizing performance and high washability.

[0025] The method for producing a deodorant fiber structure of the present invention includes an alkali treatment step in which the fiber structure is treated with an aqueous solution containing an alkaline substance, and an organic acid treatment step in which the fiber structure is then immersed and heated in an aqueous solution containing an organic acid. The alkali treatment step is preferably at least one selected from a bleaching treatment and an alkali weight reduction treatment. Bleaching can be performed by a conventional method, and treatment with an oxygen-based bleaching agent such as an aqueous solution of hydrogen peroxide is preferable. Chlorine-based bleaching agents such as an aqueous solution containing sodium hypochlorite are not preferable because they damage polyurethane elastic fibers. The organic acid treatment is preferably performed before or after dyeing. It is particularly preferable to dye the fiber after the organic acid treatment. In this way, vivid dyeing can be achieved.

[0026] When the odor eliminating fiber structure contains natural fibers such as cotton and hemp, it is preferable to include the following steps. (1) Scouring process (2) Bleaching process (3) Dyeing process (4) Flexibility process (5) A processing step in which the organic acid is immersed in an aqueous solution and heated. Of the above steps, (1) to (4) can be performed by conventional methods. The refining step and the bleaching step may be performed in the same step. In the dyeing step, the fabric can be dyed in various colors. In the processing step (5), padding treatment is also possible in addition to immersion heating, but immersion heating in a batch process is preferred from the viewpoint of deodorizing performance. The concentration of the organic acid in the aqueous solution containing the organic acid is preferably 0.5 to 10 g / L. As described above, it is preferable to dye the material after the organic acid treatment.

[0027] Next, the case where the deodorizing fiber containing the inorganic layered deodorant is an elastic fiber will be described. The elastic fiber may be a polyester-based elastic fiber, a polyamide-based elastic fiber, a polyolefin-based elastic fiber, a polyurethane-based elastic fiber, or the like, and among these, a polyurethane-based elastic fiber is preferable. The deodorant is mixed into the elastic fiber.

[0028] In the present invention, the polyurethane used for the polyurethane constituting the elastic fiber may be any polyurethane containing a structure in which the starting materials are polymer diol and diisocyanate, and is not particularly limited. The synthesis method is also not particularly limited. That is, for example, it may be polyurethane urea made from polymer diol, diisocyanate, and low molecular weight diamine, or it may be polyurethane urethane made from polymer diol, diisocyanate, and low molecular weight diol.

[0029] In the present invention, the polymer diol compound refers to a diol compound having a number average molecular weight (hereinafter sometimes abbreviated as molecular weight) of 200 or more, and a diol compound having a molecular weight of less than 200 is called a low molecular weight diol compound. The molecular weight of the polymer diol is preferably 1000 to 8000, more preferably 1500 to 6000. Polyurethane urea using a compound having a hydroxyl group and an amino group in the molecule as a chain extender may also be used. It is also preferable to use a polyfunctional glycol or isocyanate having a functionality of 3 or more within a range that does not impair the effects of the present invention.

[0030] As the polymer diol, polyether-based glycols, polyester-based glycols, polycarbonate diols, etc. are preferred. In particular, from the viewpoint of imparting flexibility and elongation to the yarn, it is preferred to use polyether-based glycols. Specific examples of polyether glycols include polyethylene glycol, modified polyethylene glycol, polypropylene glycol, polytrimethylene ether glycol, polytetramethylene ether glycol (hereinafter abbreviated as PTMG), modified PTMG which is a copolymer of tetrahydrofuran (hereinafter abbreviated as THF) and 3-methyl-THF, modified PTMG which is a copolymer of THF and 2,3-dimethyl-THF, modified PTMG which is a copolymer of THF and neopentyl glycol, and random copolymers in which THF and ethylene oxide and / or propylene oxide are irregularly arranged. One or more of these polyether glycols may be used. Among them, PTMG or modified PTMG is preferred. Next, as diisocyanates, aromatic diisocyanates such as diphenylmethane diisocyanate (hereinafter abbreviated as MDI), tolylene diisocyanate, 1,4-diisocyanate benzene, xylylene diisocyanate, and 2,6-naphthalene diisocyanate are suitable because they can obtain elastic threads made of polyurethane with particularly high heat resistance and strength. Furthermore, as alicyclic diisocyanates, for example, methylene bis(cyclohexyl isocyanate), isophorone diisocyanate, methylcyclohexane-2,4-diisocyanate, methylcyclohexane-2,6-diisocyanate, cyclohexane-1,4-diisocyanate, hexahydroxylylene diisocyanate, hexahydrotolylene diisocyanate, and octahydro-1,5-naphthalene diisocyanate are preferred. Aliphatic diisocyanates can be effectively used to suppress yellowing of elastic threads made of polyurethane. These diisocyanates may be used alone or in combination of two or more kinds.

[0031] The chain extender used in the polyurethane is preferably at least one of low molecular weight diamines and low molecular weight diols, and may be one having a hydroxyl group and an amino group in the molecule, such as ethanolamine. Examples of low molecular weight diamines include ethylenediamine, 1,2-propanediamine, 1,3-propanediamine, hexamethylenediamine, p-phenylenediamine, p-xylylenediamine, m-xylylenediamine, p,p'-methylenedianiline, 1,3-cyclohexyldiamine, hexahydrometaphenylenediamine, 2-methylpentamethylenediamine, and bis(4-aminophenyl)phosphine oxide. It is preferable to use one or more of these. Ethylenediamine is particularly preferable. By using ethylenediamine, it is possible to easily obtain threads that are excellent in elongation, elastic recovery, and heat resistance. A triamine compound capable of forming a crosslinked structure, such as diethylenetriamine, may be added to these chain extenders to an extent that the effect is not lost. In addition, typical examples of low molecular weight diols include ethylene glycol, 1,3 propanediol, 1,4 butanediol, bishydroxyethoxybenzene, bishydroxyethylene terephthalate, and 1-methyl-1,2-ethanediol. It is preferable to use one or more of these. Particularly preferable are ethylene glycol, 1,3 propanediol, and 1,4 butanediol. When these are used, the heat resistance of the diol-extended polyurethane is increased, and an elastic thread made of polyurethane having a higher strength can be obtained.

[0032] It is also preferable to use one or more kinds of terminal blocking agents in the polyurethane in combination. Examples of the terminal blocking agent include monoamines such as dimethylamine, diisopropylamine, ethylmethylamine, diethylamine, methylpropylamine, isopropylmethylamine, diisopropylamine, butylmethylamine, isobutylmethylamine, isopentylmethylamine, dibutylamine, and diamylamine, monools such as ethanol, propanol, butanol, isopropanol, allyl alcohol, and cyclopentanol, and monoisocyanates such as phenylisocyanate.

[0033] The content of the deodorant is preferably in the range of 0.5% by mass or more and 10% by mass or less with respect to the total mass of the elastic fiber made of polyurethane. By making the content of the deodorant 0.5% by mass or more, a higher ammonia gas deodorant property can be obtained when the fabric is made, which is preferable. More preferably, it is 1.0% by mass or more. On the other hand, if the content exceeds 10% by mass, it is not preferable in terms of deterioration of the stretching property and cost. More preferably, it is 7.0% by mass or less. Considering the balance between deodorant property, physical properties, and cost, the range of 1.5% by mass or more and 5.0% by mass or less is particularly preferable.

[0034] From the viewpoint of suppressing clogging of the spinneret with the spinning dope, the deodorant preferably has an average primary particle size of 3.0 μm or less, more preferably 1.5 μm or less. From the viewpoint of dispersibility, if the average primary particle size is smaller than 0.05 μm, the coagulation force increases and it becomes difficult to mix uniformly in the spinning dope, so the average primary particle size is preferably 0.05 μm or more, more preferably 0.15 μm or more.

[0035] Furthermore, the polyurethane elastic fiber may contain various stabilizers, pigments, etc. For example, light fasteners, antioxidants, etc., preferably contain hindered phenol-based agents such as BHT and "Sumilizer" (registered trademark) GA-80 manufactured by Sumitomo Chemical Co., Ltd., benzotriazole-based and benzophenone-based agents such as various "Tinuvin" (registered trademark) manufactured by Ciba-Geigy Co., Ltd., phosphorus-based agents such as "Sumilizer" (registered trademark) P-16 manufactured by Sumitomo Chemical Co., Ltd., various hindered amine-based agents, various pigments such as iron oxide and titanium oxide, inorganic substances such as zinc oxide, cerium oxide, magnesium oxide, calcium carbonate, and carbon black, fluorine-based or silicone-based resin powder, metal soaps such as magnesium stearate, lubricants such as silicone and mineral oil, various antistatic agents such as cerium oxide, betaine, and phosphoric acid, and it is also preferable that these are bonded to polyurethane. In order to further increase the durability to light and various nitrogen oxides, it is also preferable to contain a nitrogen oxide scavenger such as HN-150 manufactured by Nippon Hydrazine Co., Ltd., a thermal oxidation stabilizer such as "Sumilizer" (registered trademark) GA-80 manufactured by Sumitomo Chemical Co., Ltd., and a light stabilizer such as "Sumisorb" (registered trademark) 300#622 manufactured by Sumitomo Chemical Co., Ltd. The concentration of the polyurethane spinning solution thus obtained is usually preferably in the range of 30% by mass or more and 80% by mass or less. The deodorant is mixed into this spinning solution.

[0036] The polyurethane elastic fiber of the present invention can be obtained by, for example, dry spinning, wet spinning, or melt spinning the spinning solution constituted as above, and winding it up. Among them, dry spinning is preferred from the viewpoint of stable spinning at any fineness from thin to thick.

[0037] The fineness, cross-sectional shape, etc. of the polyurethane elastic fiber of the present invention are not particularly limited. For example, the cross-sectional shape of the yarn may be circular or flat. The dry spinning method is not particularly limited, and spinning conditions suitable for the desired properties and spinning equipment may be appropriately selected. For example, the permanent deformation rate and stress relaxation of the polyurethane elastic fiber of the present invention are particularly susceptible to the influence of the speed ratio of the godet roller and the winder, and therefore it is preferable to appropriately determine this depending on the intended use of the yarn. That is, from the viewpoint of obtaining a polyurethane elastic fiber having a desired permanent set rate and stress relaxation, it is preferable to wind the fiber with a speed ratio between the godet roller and the winder in the range of 1.10 to 1.65. In order to obtain a polyurethane elastic fiber having a particularly low permanent set rate and low stress relaxation, it is more preferable to wind the fiber with a speed ratio between the godet roller and the winder in the range of 1.15 to 1.4, and even more preferable to wind the fiber with a speed ratio between 1.15 to 1.35. On the other hand, in order to obtain a polyurethane elastic fiber having a high permanent set rate and high stress relaxation, it is preferable to wind the fiber with a speed ratio between the godet roller and the winder in the range of 1.25 to 1.65, and more preferably to wind the fiber with a speed ratio between 1.35 to 1.65.

[0038] In addition, the spinning speed is preferably 300 m / min or more from the viewpoint of improving the strength of the resulting polyurethane elastic fiber.

[0039] To apply the oil to the elastic fiber, it is preferable to apply the oil as is without diluting it with a solvent or the like, i.e., so-called neat oiling. The application process may be a process between spinning and winding into a package, a process of rewinding the wound package, a process of warping with a warping machine, or the like, but any process may be used, and the application method may be a known method such as roller oiling, guide oiling, or spray oiling. The amount of oil applied is preferably 0.1 to 5% by mass based on the elastic fiber. EXAMPLES

[0040] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these embodiments. First, the methods for evaluating various characteristics in the present invention will be described below. [Method of evaluating deodorizing properties] In accordance with the deodorizing test described in the SEK Mark Textile Product Certification Standard (established by: Textile Evaluation Technology Council, Product Certification Department, revised on April 1, 2015), the odorous component deodorizing evaluation was performed using the detector tube method. Ammonia was used as the odorous component. The initial concentration of odorous components was 100 ppm ammonia. For the blank test, a 5 L sample bag (made of film) was filled with only the odorous components for each component, sealed, and left for 2 hours, after which the remaining gas concentration was measured using a gas detector tube corresponding to each component, and this was taken as the blank test concentration. Next, the sample to be used for the measurement (10 cm x 10 cm) was placed in a sample bag (made of film), filled with the odorous components of the specified concentration described above, sealed, and the remaining gas concentration after 2 hours was measured using a gas detector tube, and this was taken as the measured concentration. The measurement was carried out three times, and the average value was used to calculate the reduction rate of the remaining gas concentration according to the following formula, and this was expressed as the reduction rate. Deodorizing component reduction rate (%) = ((blank test concentration - measured concentration of each sample) / blank test concentration)) x 100 The evaluation criteria for the reduction rate were: ammonia 70% or more, acetic acid 70% or more, isovaleric acid 85% or more, and nonenal 75% or more. [Washing instructions] In accordance with the standard washing method described in the Washing Method for SEK Mark Textile Products (established by: Japan Textile Evaluation Technology Council, Product Certification Department, revised on April 1, 2014), a household electric washing machine specified in washing method 103 described in JIS L 0217: 1995. "Display symbols and their display methods for handling textile products" was used, and JAFET standard blended detergent (blended with polyoxyethylene alkyl ether and sodium alpha-olefin sulfonate) was added at a ratio of 40mL to 30L of water at 40°C to make a washing liquid. The sample and, if necessary, a load cloth were added so that the bath ratio was 1:30, and the cycle of washing for 5 minutes, spin-drying, rinsing for 2 minutes, spin-drying, rinsing for 2 minutes, and spin-drying was repeated 10 times, and the cloth was hung to dry. [Dough pH] Measurements were performed according to the "Testing Method for Woven and Knit Fabrics" stipulated in JIS L1096:2010 8.37. 50 ml of distilled water was poured into a glass flask and boiled for 2 minutes, after which 5.0 g of finely cut fabric test pieces were added, the flask was plugged and left for 30 minutes. After 30 minutes, the extract was adjusted to 25°C ± 2°C and the pH of the extract was measured with a pH meter.

[0041] <Interlayer distance, crystallite size and ammonia gas reduction rate of the deodorant at each treatment stage of the fiber structure> α-zirconium phosphate powder (single) was subjected to scouring / bleaching, dyeing with reactive dyes, and organic acid treatment using citric acid, and the interlayer distance, crystallite size, and ammonia gas reduction rate at each treatment stage were investigated. In addition, the interlayer distance and deodorizing function of α-zirconium phosphate powder (single) at each treatment stage of a fiber structure were also analyzed. In other words, α-zirconium phosphate powder (single) was taken out from a fiber structure at each treatment stage of scouring / bleaching, dyeing with reactive dyes, and organic acid treatment using citric acid, and the interlayer distance, crystallite size, and ammonia gas reduction rate were investigated. The method of removing the organic components from the fiber structure was as follows: using the treated fabrics of Examples 1 and 3, the organic components were completely dissolved using a solvent capable of dissolving the fibers that make up the fiber structure, and the residue was separated by centrifugation. <Inorganic layered deodorant> α-zirconium phosphate powder (average particle size 0.8 μm, volume basis by particle size distribution measurement method using laser diffraction light scattering method, cumulative particle size distribution D50 median diameter) (single substance) was used. <Powder refining and bleaching treatment> A flask was charged with 2.5g / L of sodium hydroxide solution, 3.0g / L of "WX-HC" (product name: Nicca Chemical Co., Ltd.) as a scouring agent, 0.5g / L of a chelating agent, and 5g / L of a 35% aqueous hydrogen peroxide solution as a bleaching agent, making a total of 1000mL of aqueous solution, to which 10g of α-zirconium phosphate powder was added, and while mixing, the liquid temperature was raised from 20°C to 95°C and the solution was scouring and bleaching treated for 30 minutes. The treated water was then centrifuged in a centrifuge, and the α-zirconium phosphate powder that had been scouring and bleaching treated was taken out. <Dyeing process for powder> Fluorescent whitening was carried out using reactive dyes under the following ingredients and conditions. Fluorescent whitening agent: Huntsman Japan's product name "UVITEX BHT LIQ" at 2g / L ·Buffer: Glauber's salt (sodium sulfate) 10g / L Leveling agent: 0.5g / L of "Newbon" (trade name, manufactured by Nicca Chemical Co., Ltd.) was measured out and the total amount was made into a 1000mL aqueous solution, to which the above-mentioned refined and bleached α-zirconium phosphate was added and mixed. Conditions: After dyeing at 80°C for 60 minutes, the mixture was centrifuged in a centrifuge to extract the dyed α-zirconium phosphate powder. <Organic acid treatment of powder with citric acid> The dyed α-zirconium phosphate was added to 1000 mL of a 10 g / L aqueous solution of citric acid, mixed, and treated at 70°C for 20 minutes. Then, the mixture was centrifuged in a centrifuge to extract the organic acid-treated α-zirconium phosphate powder. In addition to the untreated α-zirconium phosphate powder, the deodorizing properties of the refined and bleached α-zirconium phosphate powder obtained as described above (after refined and bleached treatment), the dyed α-zirconium phosphate powder (after dyeing treatment), and the organic acid treated α-zirconium phosphate powder (after organic acid treatment) were evaluated. <Interlayer distance, crystallite size> The interlayer distance and crystallite size were measured by powder X-ray diffraction analysis using Cu-Kα radiation and a Ni plate as a filter. The crystal structure was identified by comparing the obtained diffraction pattern with ASTM cards or existing literature. The interlayer distance was analyzed by wide-angle X-ray diffraction. The results are summarized in Figure 1 and Tables 2 to 4. The horizontal axis of Figure 1 is a multiple plot (overlap) of the wide-angle X-ray diffraction patterns of each sample, and is an enlarged view of the vicinity of 2θ=10°. In Figure 1, 2θ of 9° is 1.0 nm, and 2θ of 11.7° is 0.75 nm. Table 2 shows the analysis results of the powder treatment, Table 3 shows the analysis results of the deodorant removed from the treated cloth of Example 1, and Table 4 shows the analysis results of the deodorant removed from the treated cloth of Example 3.

[0042] [Table 2]

[0043] [Table 3]

[0044] [Table 4]

[0045] As is clear from Tables 2 to 4, the deodorizing function of the α-zirconium phosphate powder deodorant was significantly reduced after scouring and bleaching treatment, but it was confirmed that it was restored by organic acid treatment. It was also confirmed that the interlayer distance was about 1.0 nm after scouring and bleaching treatment, but returned to 0.75 nm by organic acid treatment. Next, the deodorants after dyeing and organic acid treatment were identified using standard data from wide-angle X-ray diffraction. The results are shown in Table 5.

[0046] [Table 5]

[0047] As is clear from Table 5, sodium and potassium compounds were identified in the inorganic layered deodorant after dyeing treatment. In addition, sodium and potassium disappeared from the inorganic layered deodorant after organic acid treatment, and the original zirconium phosphate was identified. From the above, it was found that inorganic layered deodorants that do not have sodium or potassium bound to them have a high ammonia deodorizing function, while inorganic layered deodorants that have sodium or potassium bound to them have a lower ammonia deodorizing function. From the above experiments using the inorganic layered deodorant powder, it is understood that any spinning solution can be used as long as it can be mixed with the inorganic layered deodorant.

[0048] Example 1 <Textile material> Cotton yarn: Commercially available spun cotton yarn (metric count 40, single yarn) was used. The polyurethane elastic fiber used was 33decitex, an elastic thread made of polyurethane containing 4% by mass of α-zirconium phosphate as an inorganic layered deodorant. <Knitting> Using the above cotton yarn and elastic yarn, a knitted fabric was made on a circular knitting machine with a gauge number of 28. The weight of the knitted fabric obtained was 165 g / m 2 The mass ratio was 91.1% by mass of cotton yarn and 8.9% by mass of elastic yarn. The obtained knitted fabric is called greige fabric. <Scouring and bleaching treatment> The dyeing machine was charged with 2.5g / L of sodium hydroxide solution, 3.0g / L of "WX-HC" (product name: NICCA Chemical Co., Ltd.) as a scouring agent, 0.5g / L of a chelating agent, and 5g / L of 35% hydrogen peroxide solution as a bleaching agent, and the total amount of the aqueous solution was 20L. 1000g of knitted fabric was immersed in this aqueous solution, and the temperature of the solution was raised from 20℃ to 95℃ for 30 minutes for scouring and bleaching treatment. Next, the treated water was drained, clean water was added, and the solution was heated to 50℃ and washed with hot water for 5 minutes. Next, the hot water was drained, 0.25g / L of 90% acetic acid was added, the solution was heated to 40℃ and mixed for 5 minutes, the acetic acid water was drained, clean water was added again, the solution was heated to 50℃ and washed with hot water for 5 minutes, and then dehydrated and dried. <Dyeing process> Fluorescent whitening was carried out using reactive dyes under the following ingredients and conditions. Fluorescent whitening agent: Huntsman Japan product name "UVITEX BHT LIQ" 0.15% owf ·Buffer: Glauber's salt (sodium sulfate) 10g / L Leveling agent: "Newbon" manufactured by Nicca Chemical Co., Ltd. 0.5g / L Conditions: Dyeing process at 80°C for 60 minutes, neutralization process at 60°C for 10 minutes, soaping process at 60°C for 10 minutes, washing process at 60°C for 10 minutes, and then dehydration and drying. <Soft processing> The fabric was softened in an aqueous solution containing 1.5 owf% of "Softex A-1017S" manufactured by Kitahiro Chemical Co., Ltd. as a fabric softener at 40°C for 20 minutes, washed with water at 20°C for 5 minutes, and then dehydrated and dried. <Organic acid treatment with citric acid> The dyed knitted fabric was immersed in a dyeing machine with a 10 g / L aqueous solution of citric acid and treated at 70° C. for 20 minutes, then washed, dehydrated and dried. The knitted fabric thus obtained after treatment with citric acid was evaluated.

[0049] Example 2 The same procedure as in Example 1 was repeated except that a 5 g / L aqueous solution of citric acid was used.

[0050] Comparative Example 1 The above greige fabrics were evaluated.

[0051] Comparative Example 2 The knitted fabrics after the above scouring and bleaching treatments were evaluated.

[0052] Comparative Example 3 The knitted fabric after the above dyeing treatment was evaluated.

[0053] Comparative Example 4 The knitted fabric after the softening treatment was evaluated.

[0054] The above conditions and results are summarized in Tables 6 and 7.

[0055] [Table 6]

[0056] [Table 7]

[0057] From Comparative Examples 1 and 2 in Table 6, when knitted fabrics made of elastic fiber and cotton yarn are scoured and bleached, the deodorizing performance of the elastic fiber is reduced, and is further reduced by fluorescent whitening treatment and softening treatment. However, it was confirmed that the fabrics soaked in citric acid and heated had high deodorizing performance and also had high washing durability.

[0058] Example 3 <Textile material> The procedure was the same as in Example 1, except that a blended spun yarn (metric count 40, single yarn) consisting of 30% by mass of acrylic fiber and 70% by mass of cotton fiber was used instead of the cotton yarn. The mass proportions of the knitted fabric were 27% by mass of acrylic fiber, 62% by mass of cotton fiber, and 11% by mass of elastic fiber. <Dyeing process> In addition to the procedure of Example 1, fluorescent whitening was carried out using a cationic dye. Fluorescent whitening agent: Huntsman Japan product name "UVITEX AC LIQ" 0.3% owf Leveling agent: Nissei Chemical Industries, Ltd. product name "Nichilon Salt C-25" 0.5% owf Acid: 0.5g / L acetic acid solution Conditions: Dyeing process was carried out at 40°C for 10 minutes, 75°C for 15 minutes, and 100°C for 45 minutes, followed by soaping at 60°C for 10 minutes, washing with hot water at 60°C for 10 minutes, and then dehydrating and drying. After the acrylic was subjected to fluorescent whitening treatment, the cotton was subjected to fluorescent whitening treatment in the same manner as in Example 1. Other than the above, the treatment was the same as in Example 1.

[0059] Example 4 The same procedure as in Example 3 was repeated except that a 5 g / L aqueous solution of citric acid was used.

[0060] Comparative Example 5 The knitted fabric after the above scouring and bleaching treatment was evaluated.

[0061] Comparative Example 6 The knitted fabric after the softening treatment was evaluated. The above conditions and results are summarized in Table 8.

[0062] [Table 8]

[0063] As is clear from Table 8, knitted fabrics made of blended spun yarn of elastic fiber and acrylic / cotton fiber were bleached and treated with citric acid, and had high deodorizing performance and washing durability.

[0064] (Examples 5 to 8) (1) The yarns used were as follows: Cotton yarn: Commercially available spun cotton yarn (metric count 40, single yarn) was used. The polyurethane elastic fiber used was 22decitex, an elastic thread made of polyurethane containing 4% by mass of α-zirconium phosphate as an inorganic layered deodorant. (2) The fabric was as follows: The cotton yarn and elastic yarn were used to knit a fabric on a circular knitting machine with a gauge of 28. The fabric had a weight of 160 g / m 2 The mass proportions were 94.4% cotton yarn and 5.6% elastic yarn. (3) Post-processing The same procedure as in Example 1 was carried out except for the conditions shown in Table 9. The conditions and results are summarized in Table 9.

[0065] [Table 9]

[0066] As is clear from Table 9, the organic acids acetic acid, malic acid, citric acid, and maleic acid were also able to provide a deodorizing treatment that was wash-resistant.

[0067] Example 9 (1) The yarns used were as follows: Cotton yarn: Commercially available spun cotton yarn (metric count 40, single yarn) was used. The polyurethane elastic fiber used was 22decitex, an elastic thread made of polyurethane containing 4% by mass of α-zirconium phosphate as an inorganic layered deodorant. (2) The fabric was as follows: The cotton yarn and elastic yarn were used to knit a fabric on a circular knitting machine with a gauge of 28. The fabric had a weight of 160 g / m 2 The mass proportions were 93.1% cotton yarn and 6.9% elastic yarn. (3) Post-processing The same procedure as in Example 1 was carried out except as shown in Table 10. The conditions and results are summarized in Table 10. The whiteness was determined by measuring X, Y, Z, x, and y of the dyed fabric using a spectrophotometer (manufactured by KONICA MINOLTA, model: CM-3700d, D65 light source) in accordance with JIS Z 8715-1999. A higher value indicates whiter fabric.

[0068] [Table 10]

[0069] Example 10 The same procedures as in Example 9 were carried out except that the order of dyeing and organic acid treatment was changed, that is, the organic acid treatment was carried out first and the dyeing was carried out afterwards. The conditions and results are summarized in Tables 10 and 11.

[0070] [Table 11]

[0071] [Table 12]

[0072] As is clear from Examples 9 and 10, it was confirmed that the whiteness was higher when the organic acid treatment was performed first and the dyeing was performed later. Furthermore, from Table 12, it was confirmed that the deodorizing function of the deodorizer α-zirconium phosphate powder was significantly reduced after scouring and bleaching treatment, but the deodorizing function was restored even if the organic acid treatment was performed first and then dyeing was performed. [Industrial Applicability]

[0073] The deodorizing fiber structure of the present invention is excellent in deodorizing sweat odor and aging odor, and is suitable for carpets, curtains, bedding, underwear, diapers, sanitary products, etc. It is particularly suitable for stretchable clothing such as leg wear, innerwear, sportswear, and socks.

Claims

1. A bleached odor-eliminating fiber structure comprising a first fiber which is at least one selected from synthetic fibers and regenerated fibers, and a second fiber which is a natural fiber, The first fiber is a deodorizing fiber in which an inorganic layered deodorizing agent is mixed with a polymer, The inorganic layered deodorant has an interlayer distance of 0.1 nm or more and 0.9 nm or less and a crystallite size of 1 nm or more and 30 nm or less, The deodorizing fiber structure is characterized in that the ammonia gas reduction rate after 0 home washing and after 10 home washings is 70% or more.

2. 2. The odor eliminating fiber structure according to claim 1, wherein the inorganic layered deodorant is at least one selected from the group consisting of α-zirconium phosphate, α-hafnium phosphate, and α-titanium phosphate.

3. 3. The deodorizing fiber structure according to claim 1, wherein the deodorizing fiber constitutes 1 to 99 mass % of the fiber structure when the fiber structure is used as a parameter.

4. 3. The odor eliminating fiber structure according to claim 1, wherein the fiber structure is a knitted fabric, a woven fabric, or a garment sewn therefrom.

Citation Information

Patent Citations

  • Dyeable aramid filament fiber structure and method for producing the same

    JP2010007222A

  • Deodorant fabric

    JP2016006242A

  • Fiber structure and production method for same

    WO2016104573A1

  • Dyeable polyolefin fiber and fibrous structure comprising same

    WO2019142718A1

  • Sanitary shorts

    JP2002000659A